Simulation of vortex induced vibration of a bluff body structure - Malik Fesal, Siti Natasha (2015)
Understanding Vortex induced vibration (VIV) phenomenon is essential as it plays important role in designing marine risers which used in oil extraction from the seabed to the offshore platforms were exposed to external flows that may trigger dangerous VIV oscillations. The present two-dimensional numerical simulations of circular bluff body is a continuation of previous efforts trying to study the effect of frequency and amplitudes of the cylinder oscillation that is confined in the cross-flow and inline flow separately. The k-ε turbulence model is used to simulate the turbulent flow to evaluate the drag and lift coefficient of circular towards the flow characteristics which used time independent test (transient) and tested at different Reynolds number between 10000 and 100000 with uniform velocities of 1.35m/s and 13.5m/s. Results from dynamic response of a cylinder bluff body vibrating at frequencies variation of 1.48 Hz, 2.77 Hz and 3 Hz within 0.3m, 0.5m and 0.7m amplitudes variation were observed in this study. It is shown that for inline flow, the vibration at 0.3m amplitude is significantly low for drag and lift coefficient value for Re at 100000 compared to Re at10000. Meanwhile for the cross flow value it is observed that gives high percentages with 39% of drag coefficient and with 59% of lift coefficient compare to inline flow at high amplitude. However at low mode amplitude the cross flow contributes more with 19% of drag coefficient and 11% for lift coefficient compare to inline flow. The result also show that the cylinder oscillate higher at frequency shedding value with higher magnitude for the cross flow compare to the inline flow. Consequently, in order to get better performance, the vortex modes in the wake of oscillating cylinder have been found to be dependent on the amplitude distribution along the length of the model. The results concludes that in order to avoid inevitable vibration it is advisable by increasing damping or splitter when designing marine riser to generate more stable vortex shedding frequency.